Patterns and determinants of blood transfusion in intensive care in Sweden between 2010 and 2018: A nationwide, retrospective cohort study. Issue 6 (31st May 2022) - Holmqvist, Jacob; Brynolf, Anne; Zhao, Jingcheng; Halmin, Märit; Hollenberg, Jacob; Mårtensson, Johan; Bell, Max; Block, Linda; Edgren, Gustaf
Abstract: Background: Intensive care unit (ICU) patients are transfused with blood products for a number of reasons, from massive ongoing hemorrhage, to mild anemia following blood sampling, combined with bone marrow depression due to critical illness. There's a paucity of data on transfusions in ICUs and most studies are based on audits or surveys. The aim of this study was to provide a complete picture of ICU‐related transfusions in Sweden. Methods: We conducted a register based retrospective cohort study with data on all adult patient admissions from 82 of 84 Swedish ICUs between 2010 and 2018, as recorded in the Swedish Intensive Care Register. Transfusions were obtained from the SCANDAT‐3 database. Descriptive statistics were computed, characterizing transfused and nontransfused patients. The distribution of blood use comparing different ICUs was investigated by computing the observed proportion of ICU stays with a transfusion, as well as the expected proportion. Results: In 330, 938 ICU episodes analyzed, at least one transfusion was administered for 106, 062 (32%). For both red‐cell units and plasma, the fraction of patients who were transfused decreased during the study period from 31.3% in 2010 to 24.6% in 2018 for red‐cells, and from 16.6% in 2010 to 9.4% in 2018 for plasma. After adjusting for a range of factors, substantial variation in transfusion frequency remained, especially for plasma units. Conclusion: Despite continuous decreases in utilization, transfusions remain common among Swedish ICU patients. There is considerable unexplained variation in transfusion rates. More research is needed to establish stronger critiera for when to transfuse ICU patients.